The Relationship of Costume Design in Film With the Interest of Young Adult Women as Fashion Product Consumers in Indonesia - Adina Fairuz (Eduvest - Journal of Universal Studies, 2021)
This study discusses the relationship between costume design in films and the interest of the audience, especially young adult women, triggers of their interest in similar fashion products as consumers by using outfit styles from three films, The Devil Wears Prada (2006), Sex and The City: The Movie (2008) and Crazy Rich Asians (2018), which were selected through a questionnaire answered by 20 experts in the fashion field. The analysis was conducted on 258 young adult women (18-24 years old) domiciled in Indonesia through a questionnaire to find out their perceptions and preferences on outfit styles from the costume designs in those three films. Based on this analysis, it can be seen that if the audience is interested and feels that the outfit worn by the character fits them, then they will have the desire to wear fashion products that are similar to the appearance of the costume design in the film.